Caesar as Title and Name: The Dual Function of καῖσαρ in Mark 12.14-17 - Delgado Gómez, Alfredo ca. 20./21. Jh. (Journal for the study of the New Testament, 2026)
Much has been written about Mark's pericope on the payment of taxes to Caesar (Mk 12.14-17), but there has been no analysis of whether the word ?α?σα? functions as a title or a proper name. Nor is there a clear consensus as to when the cognomen Caesar became a title referring to the emperor and when the word καῖσαρσα became a loanword integrated in Greek. This article analyses the evolution of the meaning of CaesarCaesar/καῖσαρ as well as its functions in Mk 12.14?17. The proposal made here is that the word καῖσαρ functions in Mk 12.14-17 simultaneously as a proper name and a title. This deliberate ambiguity allows the scene to function meaningfully both for Jesus?s context and the author's own.